2020
DOI: 10.1111/trf.16094
|View full text |Cite
|
Sign up to set email alerts
|

Effect of platelet storage duration on clinical outcomes and incremental platelet change in critically ill children

Abstract: Background The safety of platelet (PLT) concentrates with longer storage duration has been questioned due to biochemical and functional changes that occur during blood collection and storage. Some studies have suggested that transfusion efficacy is decreased and immune system dysfunction is worsened with increased storage age. We sought to describe the effect of PLT storage age on laboratory and clinical outcomes in critically ill children receiving PLT transfusions. Study Design and Methods: We performed a se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Two small randomized studies on PC storage duration found no TRALI cases, but were likely underpowered to find any, as their focus was on platelet count increment and transfusion intervals 23,24 . An individual patient data meta‐analysis of PC storage duration found no relation with in‐hospital mortality, 36 and neither did two retrospective and one prospective cohort study 37–39 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two small randomized studies on PC storage duration found no TRALI cases, but were likely underpowered to find any, as their focus was on platelet count increment and transfusion intervals 23,24 . An individual patient data meta‐analysis of PC storage duration found no relation with in‐hospital mortality, 36 and neither did two retrospective and one prospective cohort study 37–39 …”
Section: Discussionmentioning
confidence: 99%
“…23,24 An individual patient data meta-analysis of PC storage duration found no relation with in-hospital mortality, 36 and neither did two retrospective and one prospective cohort study. [37][38][39] Intervention Saline Fresh Platelets Aged Platelets F I G U R E 3 Blood cell counts and inflammatory biomarkers changed after infusion of lipopolysaccharide. The light gray area represents the time before transfusion, and the dark gray area represents the time after transfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, the importance of storage duration of platelets is unclear. 29 Though metabolomic changes have been described with increasing irradiation storage duration, it is unclear if the transfusion of aged platelets has clinical repercussions. 30 Infants and children in our cohort were more likely to be transfused single products in the ICU and general ward and multiple products in the OR.…”
Section: Discussionmentioning
confidence: 99%
“…In our cohort, slightly more than half of infants and children were transfused with ABO identical platelets, demonstrating a population in which equipoise exists to explore this clinical question. Likewise, the importance of storage duration of platelets is unclear 29 . Though metabolomic changes have been described with increasing irradiation storage duration, it is unclear if the transfusion of aged platelets has clinical repercussions 30 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation